Urban-Rural Health Insurance Integration and China’s Rural Household Savings - Yuan Z; Zhang F; Li Z; Wei H (Dove Medical Press, 2024)
Zhen Yuan,1,2 Fan Zhang,3 Zhiguang Li,1,2 Hua Wei1,2 1School of Economics and Management, Anhui University of Chinese Medicine, Hefei, Anhui, People's Republic of China; 2Key Laboratory of Data Science & Innovative Development of Traditional Chinese Medicine, Philosophy and Social Sciences of Anhui Province, Hefei, Anhui, People's Republic of China; 3School of Finance, Nanjing Agricultural University, Nanjing, Jiangsu, People's Republic of ChinaCorrespondence: Zhiguang Li; Hua Wei, Email lizhiguang0731@163.com; weihua@ahtcm.edu.cnBackground: A linchpin to realizing the internal circulation (referring to the domestic cycle of production, distribution and consumption) is reducing residents' saving rate and expanding the domestic needs. However, rural residents in China demonstrate a strong propensity to save money.Methods: In light of practical characteristics of urban-rural health integration promoted in different places, the three-phase data (from 2014 to 2018) and the dual difference-in-differences model of the China Labor-force Dynamics Survey (CLDS) are used to empirically investigate the impact of urban-rural health insurance integration on rural household savings.Results: Research reveals that urban-rural health integration can reduce the health risks and medical risks facing rural households, thus weakening the motivation of precautionary savings. The analysis of heterogeneity reveals that the integration of urban-rural health insurance significantly influences the savings rates of households headed by older individuals, particularly women, with lower levels of educational attainment. Besides, the single-tier health insurance system can have a more significant impact, whereas the multi-tier insurance system may not significantly affect the savings rate.Conclusion: Based on the aforesaid research conclusions, this article believes that in order to reduce the savings rate of rural households and expand consumption, the health insurance system should be further improved.Keywords: urban-rural health insurance integration, rural household, savings rate, health risks, medical risks